Multi ping-pong and an entropy estimate in groups - Tarchała, Katarzyna; Walczak, Paweł (Annales Mathematicae Silesianae, 2018)
We provide an entropy estimate from below for a finitely generated group of transformation of a compact metric space which contains a ping-pong game with several players located anywhere in the group.